2019
DOI: 10.1007/s00210-019-01639-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Treatment with a brain-selective prodrug of 17β-estradiol improves cognitive function in Alzheimer’s disease mice by regulating klf5-NF-κB pathway

Abstract: 10β,17β-dihydroxyestra-1,4-dien-3-one (DHED) which is a brain-selective prodrug of 17β-estradiol has been reported to improve the cognitive function in Alzheimer's disease (AD) mice model. However, little is known about the potential mechanism for cognitive improvement. In the present study, we used AD mice to investigate the effects and mechanisms of DHED treatment. Female Tg2576 transgenic AD mice were ovariectomized and then treated by implanting Alzet osmotic minipumps containing DHED or vehicle subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Thus far, DHED (Figure 3B) has been studied most extensively in preclinical animal models of E2-responsive maladies [23,36,50,51]. The unprecedented CNS selectivity of our approach in terms of prodrug bioactivation has also recently been confirmed independently from our laboratory [52,53]. We have also unambiguously shown the CNS-selective bioactivations of HEDD and αDHD to E1 and αE2, respectively [35,37].…”
Section: Bioprecursor Prodrugs For Cns-selective Estrogen Therapysupporting
confidence: 69%
See 1 more Smart Citation
“…Thus far, DHED (Figure 3B) has been studied most extensively in preclinical animal models of E2-responsive maladies [23,36,50,51]. The unprecedented CNS selectivity of our approach in terms of prodrug bioactivation has also recently been confirmed independently from our laboratory [52,53]. We have also unambiguously shown the CNS-selective bioactivations of HEDD and αDHD to E1 and αE2, respectively [35,37].…”
Section: Bioprecursor Prodrugs For Cns-selective Estrogen Therapysupporting
confidence: 69%
“…Consequently, these animals had a higher cognitive performance, similar to those treated with the parent E2, when compared to the untreated control group. An independent follow-up study not only have confirmed these promising results, but also found that DHED treatment reduced oxidative and inflammatory stress, as well as decreased phosphorylated tau (τ) protein levels in OVX transgenic AD mouse [52]. An investigation focusing on assessing DHED’s therapeutic potential in males of the APPswe/PS1dE9 DTG-mouse AD model also revealed reduction of Aβ formation and protection against Aβ-associated cognitive impairment, as summarized in Figure 7 [51].…”
Section: Bioprecursor Prodrugs For Cns-selective Estrogen Therapymentioning
confidence: 86%
“…Notably, THAP1 has been observed to have a binding site in the specificity protein 1 (Sp1) promoter in humans 31 , and Sp1 was reported to be enriched for binding motifs in AD hyperacetylated peaks in Marzi et al (2018). Amongst microglia-specific and oligodendrocyte-specific AD hyperacetylated peaks we observed significant enrichment of binding motifs for Krüppel-like transcription factor 5 (KLF5) (microglia: P < 1 × 10 −16 , oligodendrocytes: P < 1 × 10 −91 ), a transcription factor implicated in inflammatory responses 32 .…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, sex hormones were known to influence kidney disease 62 . It was reported that androgen‐induced KLF5 expression in human breast cancer cell lines and a prodrug of 17β‐oestradiol inhibited KLF5‐NFκB inflammatory pathway in the Alzheimer's Disease mouse model 63,64 . In addition, oncogenic regulator protein SET inhibited KLF5 activation by binding to its DNA‐binding domain (DBD).…”
Section: Post‐translational Transcriptional Post‐transcriptional Rementioning
confidence: 99%